EARNING MANAGEMENT: THE ROLE OF COMPANY SIZE, LEVERAGE, AND GOOD CORPORATE GOVERNANCE ON GO PUBLIC BANKING - Eni Puji Astuti; Yohanes Indrayono; Hendro Sasongko (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the influence of company size, leverage, managerial ownership, and institutional ownership on earning management practices among publicly listed banking firms in Indonesia. The study employs a quantitative approach using panel data regression analysis. The sample comprises 20 banking companies listed on the Indonesia Stock Exchange over the 2017–2023 period, yielding 140 firm-year observations. The model selection is based on the Chow and Hausman tests, with the fixed effect model selected as the best fit. The results reveal that company size, leverage, and managerial ownership have significant negative effects on earning management, indicating that larger companies, higher debt ratios, and greater managerial ownership are associated with less earnings manipulation. Conversely, institutional ownership exhibits a significant positive effect, suggesting that higher institutional ownership increases the likelihood of earning management practices, possibly driven by short-term performance pressures. The findings emphasize the importance of corporate governance mechanisms in curbing earnings management. Regulators, stakeholders, and board members should consider enhancing transparency and aligning ownership structures to mitigate opportunistic financial reporting behavior. This study provides new insights into how firm characteristics and ownership structures affect earnings management behavior in the heavily regulated banking sector of an emerging economy, extending prior agency theory and corporate governance research.